Finite-time synchronisation of memristive hyperchaotic circuit based on Lorenz system with transmission delay. (2018) - Wu, Hongjuan; Hu, Xiang; Feng, Yuming
In this paper, we analyse the characteristics of one type of circuit structure that is extended from simplified Lorenz system by taking a memristor as feedback. Considering the transmission time delay between master system and slave system, we used a compound finite-time synchronisation signal controller, which consists of a general feedback control signal and a fine adjustment signal, to ensure the synchronisation of two memristive hyperchaotic circuits based on Lorenz system. Based on Lyapunov stability theory, finite-time control, matrix inequality, and considering the transmission time delay, the finite-time synchronisation condition for this type of memristive hyperchaotic circuit based on Lorenz system with transmission time delay via finite-time controller is given. Finally, simulation results are used to verify the feasibility and effectiveness of this method.